Intermittent Oxygen Fasting and Digital Technologies: from Antistress and Hormones Regulation to Wellbeing, Bliss and Higher Mental States - Drigas, Athanasios; Mitsea, Eleni; Skianis, Charalampos (Technium BioChemMed, 2022)
Low oxygen breathing has been the subject of considerable research in recent years. The present review aims to determine the physiological and neuropsychological benefits of low-oxygen training. Specifically, we explored the ways low oxygen affects hormones, neurotransmitters and growth factors responsible for neuroplasticity, higher cognition and positive emotions. In addition, we shed light on the importance of hypoxia to expand the conscious experience. Furthermore, we investigate the role of digital technologies in assisting hypoxic training. The results showed that oxygen deprivation, under certain circumstances, has beneficial effects on cognition, mood and consciousness. It was observed an increase in growth factors, which are responsible for tissue repair and regeneration. Hypoxia also was found to stimulate the hormones of pleasure, happiness, pain tolerance, socialization and relaxation. Interestingly, people under hypoxic conditions are more likely to have transcendental experiences -even to develop ‘superhuman’ abilities. Digital technologies facilitate the safe implementation of hypoxic training enabling users to take control of a powerful tool, which is none other than breathing. Metacognition in breathing can help people consciously and safely manipulate their breathing by moving themselves away from their comfort zone and exploring new pathways to rewire their brains and plumb the depths of their physical, cognitive, emotional and spiritual potential.